Vocational Bias: A Potential Pitfall in the Use of Key Informant Interviews in Pediatric Community Needs Assessments. (2008) - Northrip, Kimberly; Chen, Candice; Marsh, Jennifer
Abstract : Key informants are individuals with insight into a community or a problem of interest. Our objective was to evaluate the effect of the employment type of key informants on the outcome of a pediatric needs assessment for an urban community. Twenty-one interviews were conducted during the course of a pediatric community needs assessment. As part of the interview, informants were asked to list the top three problems facing children in their community. We analyzed their answers to determine if informant responses differed by employment type. Key informants were divided into four employment types: health care setting, social service, business, and infrastructure. Responses were coded as being primarily one of three types: medical, social, or resource. Our results showed that those informants who worked in a health care setting listed medical problems more often than those who did not (p < 0.04). Those who worked in social services listed resource problems more often than those who did not (p < 0.05). Those in business and infrastructure positions listed more social problems (p < 0.37). No difference was observed in response type between those who had lived in the community at some point and those who had not. This study lends support to the hypothesis that informants' reporting of community problems is biased by their vocation. Clinicians often focus their needs assessments on health care workers. This study suggests, however, that we need to take into consideration the bias this presents and to seek to interview people with diverse work experiences. By limiting the process to health care workers, clinicians are likely to get a skewed perspective of a community's needs and wants.